Straight Man - Russo, Richard (Random House, 1997)
A comedy on university downsizing. To make sure the English department's budget is not cut, William Devereaux, its chairman, goes on TV threatening to kill a goose a day if that happens. Unfortunately a goose is beheaded soon after and Devereaux finds himself in hot water. The setting is Pennsylvania. By the author of Nobody's Fool.
Keywords: College teachers; Fiction; College stories; dept.eng; faculty_collection

How Many Stones?: Poems - Shipley, Vivian (Devil's Millhopper Press, 1997)
Keywords: Devil's Millhopper Press Chapbook Contest; dept.eng; faculty_collection

Oroonoko or the Royal Slave - Behn, Aphra (W.W. Norton, 1997)
Keywords: Behn; Aphra; 1640-1689. Oroonoko; Enslaved persons; Fiction; Slave trade; History; Sources; Slavery in literature; Suriname; dept.eng; faculty_collection

Opera in the flesh: Sexuality in operatic performance - Abel,S - Blackmer, CE (Journal of the History of Sexuality, 1997)
tex.unique-id: ISI:A1997YC95500010
Keywords: dept.eng; ⛔ No DOI found